Populist Eurosceptic trajectories in Italy and the Netherlands during the European crises. (August 2018) - Pirro, Andrea LP; van Kessel, Stijn
Multiple crises shook the European Union (EU) during the past decade. First, the economic and financial crises that unfolded since 2008 shook the foundations of the European project and its monetary union. Then, the inflow of migrants and asylum seekers into Europe in 2015 questioned the EU's ability to jointly respond to common political issues. More recently, Brexit came across as the corollary of a prolonged legitimacy crisis. These crises have not only affected the course of European integration but also provided novel issues for political competition within the EU member states. At the party-political level, populist anti-establishment parties have traditionally listed among the principal interpreters and drivers of criticism towards 'Europe'. In this article, we empirically address the changing Eurosceptic frames adopted by populist parties during these crises and speculate on the reverberation of these frames in respective party systems. For this purpose, we focus on two cases: Italy and the Netherlands. Both countries present instances of populist parties of different ideological persuasions within traditionally Europhile contexts. At the same time, both countries have been affected to very different extents by the recent crises, allowing us to examine how populist parties have responded to different political opportunities.